Validity of the FACT-H&N (v 4.0) among Malaysian oral cancer patients - Doss, Jennifer Geraldine; Thomson, W. Murray; Drummond, Bernadette Kathleen; Raja-Latifah, Raja Jallaludin (Elsevier, 2011)
To assess the cross-sectional construct validity of the Malay-translated and cross-culturally adapted FACT-H&N (v 4.0) for discriminative use in a sample of Malaysian oral cancer patients. A cross-sectional study of adults newly diagnosed with oral cancer. HRQOL data were collected using the FACT-H&N (v 4.0), a global question and a supplementary set of eight questions (‘MAQ’) obtained earlier in pilot work. Of the 76 participants (61.8% female; 23.7% younger than 50), most (96.1%) had oral squamous cell carcinoma; two-thirds were in Stages III or IV. At baseline, patients’ mean FACT summary (FACT-G, FACT-H&N, FACT-H&N TOI, and FHNSI) and subscale (pwb, swb, ewb, fwb, and hnsc) scores were towards the higher end of the range. Equal proportions (36.8%) rated their overall HRQOL as ‘good’ or ‘average’; fewer than one-quarter rated it as ‘poor’, and only two as ‘very good’. All six FACT summary and most subscales had moderate-to-good internal consistency. For all summary scales, those with ‘very poor/poor’ self-rated HRQOL differed significantly from the ‘good/very good’ group. All FACT summary scales correlated strongly (r > 0.75). Summary scales showed convergent validity (r > 0.90) but little discriminant validity. The discriminant validity of the FHNSI improved with the addition of the MAQ. The FACT-H&N summary scales and most subscales demonstrated acceptable cross-sectional construct validity, reliability and discriminative ability, and thus appear appropriate for further use among Malaysian oral cancer patients.